Communism, atheism, and the Orthodox Church of Albania: cooperation, survival and suppression, 1945-1967 - Hoxha, Artan R. (Routledge religion, society and government in Eastern Europe and the Former Soviet States, 2022)
"This book examines the relations between the Albanian communist regime and the Albanian Autocephalous Orthodox Church (AAOC) from 1945, when the communists came to power, to 1967, when Albania became the only atheistic state in the world, and religion of all kinds was completely suppressed. Based on extensive archival research, the book outlines Orthodox Church life under communism and considers the regime's strategies to control, use, and subordinate the Church. It argues against a simple state oppression versus Church resistance scenario, showing that the situation was much more complex, with neither the regime nor the Church being monolithic entities. It shows how, despite the brutality and the constant pressure of the state, the Church successfully negotiated with the communist authorities and benefited from engaging with them, and how the communist authorities used the Church as a tool of foreign policy, especially to strengthen the regime's ties with their East European allies"--